Development of Teaching Materials "The Negative Effects of Electric Cigarette" As a High School Student Learning Source - Erlianti, Susi; Lisdiana, Lisdiana; Widiyaningrum, Priyantini (Journal of Innovative Science Education, 2021)
Lack of awareness and limited information about the dangers of e-cigarettes among teenagers, especially high school students, make them assume that e-cigarettes are a safe alternative to reduce smoking habit. This can be circumvented through the development of teaching materials that are tailored to the needs of students. This research aims to develop teaching materials about the negative effects of e-cigarettes as a source of learning for high school students and analyze their validity, readability, and feasibility. This development research uses 4-D (Define, Design, Develop, Disseminate) design. The subjects of this research include material and media experts, students of class XI MIPA 3 and XI MIPA 4 SMAN 12 Semarang and teachers who are members of senior high school biology teachers forum in Rembang Regency. The results showed the validation scores of material and media experts were 83.00% and 97.70%, respectively, with very valid criteria. Analysis of the readability of teaching materials from the results of student responses and the cloze test, respectively obtained an average score of 86.20% and 84% with very good and independent criteria. Analysis of the feasibility of teaching materials from the results of teacher responses at the senior high school biology teachers forum in Rembang, obtained an average score of 83.70% with very feasible criteria. Based on the results of the research, it can be concluded that teaching materials about the negative effects of e-cigarettes are valid, it has good readability, and feasible to use as a source of learning for high school students. The teaching material is expected to be able to add insight and knowledge about the negative effects of e-cigarette exposure and to contribute better in improving the quality of learning resources.